Method for manufacturing ion-exchange membrane

The use of low-density polyethylene resin as a substrate for ion exchange membranes, thermally polymerized at 120 °C or less, addresses adhesion and mechanical issues, enhancing the membrane's durability and productivity.

JP2025017065APending Publication Date: 2025-02-05TOKUYAMA CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023119942
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-24
Publication Date
2025-02-05

AI Technical Summary

Technical Problem

Existing methods for manufacturing ion exchange membranes face issues with adhesion between the substrate and ion exchange resin, leading to problems such as environmental impact, high production costs, and inferior mechanical properties like drug resistance and tearability, particularly when using vinyl chloride resin fiber fabrics, while polyolefin resin fibers suffer from low adhesion and swelling.

Method used

A manufacturing method involving low-density polyethylene resin as the substrate, filled with a polymerization composition, is thermally polymerized at 120 °C or less to create a composite film, followed by introducing an ion exchange group, resulting in improved adhesion between the substrate and ion exchange resin.

Benefits of technology

The method produces an ion exchange membrane with enhanced adhesion and mechanical strength, reducing the need for long immersion times and minimizing resin peeling, thus improving productivity and durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025017065000001_ABST
    Figure 2025017065000001_ABST
Patent Text Reader

Abstract

To provide a method for manufacturing an ion-exchange membrane having excellent adhesiveness.SOLUTION: Provided is a method for manufacturing an ion-exchange membrane. The membrane includes a substrate containing linear low-density polyethylene resin and ion-exchange resin carried by the substrate. The manufacturing method includes filling polymerizable composition for forming ion-exchange resin into a substrate to obtain a first composite membrane, thermally polymerizing the first composite membrane at 100°C or higher and 120°C or lower to obtain a second composite membrane, and introducing ion-exchange group into the second composite membrane to obtain an ion-exchange membrane.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing an ion exchange membrane. [Background technology]

[0002] Ion exchange membranes include cation exchange membranes that selectively allow cations to pass through and anion exchange membranes that selectively allow anions to pass through. Ion exchange membranes are used in electrodialysis, diffusion dialysis, water electrolysis, etc.

[0003] The paste method is known as an industrial method for producing ion exchange membranes. In the paste method, a polymerizable composition containing a monomer capable of introducing an ion exchange group is filled into a substrate, the substrate is polymerized, and then the ion exchange group is introduced to produce an ion exchange membrane. For example, a woven fabric of polyvinyl chloride resin fiber or a porous membrane of polyolefin resin is used as the substrate. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 03-153740 [Patent Document 2] Japanese Patent Application Publication No. 06-322156 [Non-patent literature]

[0005] [Non-Patent Document 1] Yukio Mizutani, Synthesis of Ion Exchange Membranes by Impregnation Method, Industrial Chemistry Journal, Vol. 65, No. 7 (1962) Summary of the Invention [Problem to be solved by the invention]

[0006] A method for producing an ion exchange membrane with excellent adhesion is provided. [Means for solving the problem]

[0007] According to an embodiment, a method for producing an ion exchange membrane is provided, which includes a substrate containing a linear low-density polyethylene resin and an ion exchange resin supported on the substrate. The method includes filling the substrate with a polymerizable composition for forming an ion exchange resin to obtain a first composite membrane, thermally polymerizing the first composite membrane at 100°C or more and 120°C or less to obtain a second composite membrane, and introducing an ion exchange group into the second composite membrane to obtain an ion exchange membrane. Effect of the Invention

[0008] A method for producing an ion exchange membrane with excellent adhesion is provided. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a cross-sectional view illustrating an example of an ion exchange membrane. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Conventionally used woven fabrics of polyvinyl chloride resin fibers had excellent adhesion to ion exchange resins, but the fiber was manufactured using a solution spinning method that used organic solvents, which placed a large burden on the environment and required a solvent recovery process, which created problems in terms of production and equipment costs. Furthermore, the chemical resistance and heat resistance of the fabrics were inferior to those of polyolefin resins. On the other hand, porous membranes made of polyolefin resins tend to tear easily, and damage to the membranes during handling was an issue. Therefore, there was a demand for ion exchange membranes made of woven fabrics of polyolefin resin fibers that had high adhesion to ion exchange resins.

[0011] Patent Document 1 proposes an ion exchange membrane using a woven fabric of high-density polyethylene fibers as a substrate, and Patent Document 2 proposes an ion exchange membrane using a woven fabric of ultra-high molecular weight polyethylene fibers as a substrate. Ion exchange membranes using these woven fabrics have lower adhesion to ion exchange resins than polyvinyl chloride woven fabrics, and a large amount of polymer that does not contain ion exchange groups is added to the polymerizable composition to suppress swelling due to water absorption of the ion exchange resin and peeling of the resin from the substrate, which tends to increase the resistance of the ion exchange membrane.

[0012] In Non-Patent Document 1, a monomer capable of introducing an ion exchange group is diffused and polymerized inside a low-density polyethylene non-porous membrane by a high-pressure method. However, in order to diffuse the monomer inside the non-porous membrane, it is necessary to provide a monomer immersion time of 10 hours or more, which is an issue in productivity. Therefore, it was thought that a woven fabric of polyolefin resin fiber that does not require a long monomer immersion process and has excellent adhesion to ion exchange resins would be suitable as a substrate for ion exchange membranes, and the present invention was arrived at.

[0013] According to an embodiment, a method for producing an ion exchange membrane is provided, which includes a substrate containing a linear low-density polyethylene resin and an ion exchange resin supported on the substrate. The method includes filling the substrate with a polymerizable composition for forming an ion exchange resin to obtain a first composite membrane, thermally polymerizing the first composite membrane at 100°C or more and 120°C or less to obtain a second composite membrane, and introducing an ion exchange group into the second composite membrane to obtain an ion exchange membrane.

[0014] The ion exchange membrane obtained by the manufacturing method according to the embodiment has excellent adhesion. The present inventors believe that the reason is as follows. First, in order to improve the adhesion between the substrate and the ion exchange resin in the ion exchange membrane, it is important that the monomer for forming the ion exchange resin diffuses into the substrate. That is, it is considered that the substrate and the resin are complexed by polymerizing them in a state where they are diffused into the substrate, and the adhesion is improved. As a result of intensive research by the present inventors, it was found that it is important to heat the substrate to a temperature range of 100°C or more and 120°C or less in order to adequately diffuse the monomer into the substrate containing the linear low-density polyethylene resin. That is, by thermally polymerizing the substrate at a temperature within this range, the monomer is sufficiently diffused into the substrate, and an ion exchange membrane having high adhesion between the substrate and the ion exchange resin can be obtained.

[0015] [Ion exchange membrane] The ion exchange membrane includes a substrate and an ion exchange resin supported on the substrate. The ion exchange membrane may be a cation exchange membrane or an anion exchange membrane. The ion exchange membrane may be used in a hydrogen production device, a water electrolysis device, a fuel cell, an electrodialysis device, a diffusion dialysis device, a pure water production device, an ion-exchanged water production device, etc.

[0016] The substrate may be a woven fabric or a nonwoven fabric. From the viewpoint of mechanical strength, the substrate is preferably a woven fabric. The opening rate of the substrate is, for example, 1% or more and 60% or less. This opening rate can be calculated, for example, by observing the woven fabric from above, measuring the area of ​​the woven fabric portion and the area of ​​the void portion not including the woven fabric, and expressing it as a percentage of (area of ​​void portion) / (area of ​​fiber portion+area of ​​void portion).

[0017] The porosity of the substrate is, for example, 30% or more and 80% or less. This porosity can be calculated by cutting out a substrate with a specified area, measuring the weight and thickness, and using the resin density. It can be expressed as follows: apparent density = substrate weight / (substrate thickness x substrate area), porosity = {1 - (apparent density / resin density)} x 100.

[0018] The substrate contains a linear low density polyethylene (LLDPE) resin. The substrate typically does not contain a resin containing a fluorine atom or a chlorine atom. The substrate is preferably a woven fabric consisting of only fibers containing a linear low density polyethylene resin. The LLDPE resin fiber may be a multifilament or a monofilament. From the viewpoint of increasing the durability of the ion exchange membrane, it is preferable that the LLDPE resin fiber is a multifilament.

[0019] The thickness of the LLDPE resin fiber is, for example, 10 decitex or more and 300 decitex or less, and more preferably 30 decitex or more and 150 decitex or less.

[0020] The crystallinity of the LLDPE resin is preferably 10% or more and 60% or less. When the crystallinity is within this range, the monomer for forming the ion exchange resin is appropriately diffused inside the LLDPE resin, so that an ion exchange membrane having excellent adhesion and mechanical strength is obtained. The crystallinity of the LLDPE resin is more preferably 20% or more and 50% or less.

[0021] The crystallinity of LLDPE resin can be measured by differential scanning calorimetry (DSC). That is, first, the heat of fusion A1 of the LLDPE resin is measured. The percentage of the value (A1 / B1) obtained by dividing this heat of fusion A1 by the heat of fusion B1 of polyethylene with a degree of crystallinity of 100% is taken as the crystallinity of the LLDPE resin. The heat of fusion B1 of polyethylene with a degree of crystallinity of 100% is 286.7 J / g.

[0022] The melt mass flow rate of the LLDPE resin, measured in accordance with Japanese Industrial Standard K7210-1 under conditions of a temperature of 190° C. and a load of 2.16 kg, is, for example, 0.1 g / 10 min or more and 15 g / 10 min or less, and preferably 0.5 g / 10 min or more and 13 g / 10 min or less.

[0023] Examples of the cation exchange group of the ion exchange resin include a sulfonic acid group, a carboxylic acid group, a phosphonic acid group, and a phenolic hydroxyl group. In general, a sulfonic acid group, which is a strongly acidic group, is preferred. Examples of the anion exchange group of the ion exchange resin include a quaternary ammonium group, a pyridinium group, a triazolium group, an imidazolium group, a primary amino group, a secondary amino group, and a tertiary amino group. In general, a quaternary ammonium group or a quaternary pyridinium group, which is a strongly basic group, is preferred.

[0024] As the ion exchange resin, at least one of a hydrocarbon resin and a fluorine resin may be used. As the hydrocarbon resin, a styrene resin, an acrylic resin, or the like may be used. As the fluorine resin, a resin having a perfluorocarbon skeleton may be used. As the ion exchange resin, it is preferable to use a hydrocarbon resin, and it is more preferable to use a styrene resin. The styrene resin includes a styrene resin, a copolymer of a styrene derivative and a comonomer, and the like.

[0025] The ion exchange resin may contain a resin different from the above-mentioned main component resin. Such a resin may be at least one selected from the group consisting of chlorine-based resins and hydrocarbon-based resins. From the viewpoint of increasing the adhesion between the substrate and the ion exchange resin, it is preferable to contain a hydrocarbon-based resin, more preferable to contain a polyethylene resin, and even more preferable to contain a low-density polyethylene resin (LDPE). The ratio of these resins in the ion exchange resin is, for example, 1% by mass or more and 50% by mass or less. These other resins may be scattered in the form of particles or islands in the matrix of the ion exchange resin.

[0026] The ion exchange resin may further contain an additive such as a plasticizer. The plasticizer may be at least one selected from the group consisting of dibutyl phthalate, dioctyl phthalate, dibutyl phthalate, tributyl phosphate, and acetyl tributyl citrate. The proportion of the plasticizer in the ion exchange resin is, for example, 1% by mass or more and 20% by mass or less.

[0027] The thickness of the ion exchange membrane is, for example, 20 μm or more and 400 μm or less.

[0028] Fig. 1 is a cross-sectional view showing an example of an ion exchange membrane. The ion exchange membrane 10 shown in Fig. 1 includes a substrate 11 and an ion exchange resin 12 supported on the substrate 11. The substrate 11 is a plain weave fabric made of LLDPE fibers 1.

[0029] [Method of manufacturing ion exchange membrane] The method for producing an ion exchange membrane according to the embodiment includes filling a substrate with a polymerizable composition for forming an ion exchange resin to obtain a first composite membrane, thermally polymerizing the first composite membrane at 100° C. or more and 120° C. or less to obtain a second composite membrane, and introducing ion exchange groups into the second composite membrane to obtain an ion exchange membrane. Here, filling a substrate with a polymerizable composition means filling voids between fibers constituting the substrate with the polymerizable composition.

[0030] A method for producing an ion exchange membrane according to an embodiment may include filling a substrate with a polymerizable composition for forming an ion exchange resin to obtain a first composite membrane, stacking the first composite membrane and a release sheet and winding them into a roll to obtain a first wound body, thermally polymerizing the first wound body at 100°C or more and 120°C or less to obtain a second composite membrane, peeling the release sheet from the second composite membrane, and introducing ion exchange groups into the second composite membrane.

[0031] The release sheet may be, for example, a polyethylene terephthalate (PET) film, a polyvinyl alcohol film, a polycarbonate film, or a polytetrafluoroethylene film.

[0032] From the viewpoint of improving adhesion, the thermal polymerization temperature of the first composite membrane is preferably higher than 100° C., more preferably 105° C. or higher, and even more preferably 110° C. or higher. From the viewpoint of improving durability of the ion exchange membrane, the thermal polymerization temperature of the first composite membrane is preferably lower than 120° C., more preferably 115° C. or lower, and even more preferably 110° C. or lower. The retention time after reaching the thermal polymerization temperature is, for example, 0.5 hours or more and 10 hours or less, and preferably 1 hour or more and 6 hours or less.

[0033] The introduction of ion exchange groups is carried out, for example, by immersing the second composite membrane in a solution of a compound capable of introducing ion exchange groups. In one example, an anion exchange membrane having quaternary ammonium groups introduced therein is obtained by immersing the second composite membrane having chloromethylstyrene units in a trimethylamine solution for 12 hours or more. In another example, a cation exchange membrane having sulfonic acid groups introduced therein is obtained by contacting the second composite membrane having styrene units with concentrated sulfuric acid.

[0034] The polymerizable composition for forming the ion exchange resin contains a monomer capable of introducing an ion exchange group, and may further contain a crosslinking agent, a thickener, a polymerization initiator, and other additives.

[0035] The monomer capable of introducing an ion exchange group includes at least one selected from the group consisting of styrene, styrene derivatives, vinylpyridine, and vinylpyridine derivatives. The monomer capable of introducing an ion exchange group preferably includes at least one selected from the group consisting of styrene and styrene derivatives.

[0036] The styrene derivative may be at least one selected from the group consisting of chloromethylstyrene, vinyltoluene, vinylxylene, α-methylstyrene, vinylnaphthalene, and α-halogenated styrene.

[0037] The proportion of the monomer capable of introducing an ion-exchange group in the polymerizable composition is, for example, 10% by mass or more and 90% by mass or less, and preferably 30% by mass or more and 80% by mass or less.

[0038] The vinylpyridine derivative may be at least one selected from the group consisting of 4-vinylpyridine and 2-methyl-5-vinylpyridine.

[0039] As the crosslinking agent, a monomer having a polymerizable group with two or more functionalities is used. As the crosslinking agent, it is preferable to use at least one selected from the group consisting of divinylbenzene, divinylsulfone, butadiene, chloroprene, divinylbiphenyl, divinylnaphthalene, diallylamine, divinylpyridine, and trivinylbenzene, and it is preferable to use divinylbenzene.

[0040] The proportion of the crosslinking agent in the polymerizable composition is, for example, 30% by mass or less, and preferably 3% by mass or more and 20% by mass or less.

[0041] The thickener can be blended to increase the viscosity of the polymerizable composition to facilitate the support of the polymerizable composition on the substrate while enhancing the adhesion between the ion exchange resin and the substrate. For example, fine resin particles are used as the thickener. The resin may be at least one selected from the group consisting of chlorine-based resins and hydrocarbon-based resins. From the viewpoint of enhancing the adhesion between the substrate and the ion exchange resin, it is preferable to contain a hydrocarbon-based resin, more preferably a polyethylene resin, and even more preferably a low-density polyethylene resin (LDPE). The average particle size of the fine particles measured by the Coulter method is, for example, 0.1 μm or more and 20 μm or less.

[0042] The proportion of the thickener in the polymerizable composition is, for example, 1 mass % or more and 50 mass % or less, preferably 3 mass % or more and 30 mass % or less, and more preferably 15 mass % or more and 25 mass % or less.

[0043] The plasticizer may be at least one selected from the group consisting of dibutyl phthalate, bis(2-ethylhexyl) phthalate, and tributyl acetyl citrate. The proportion of the plasticizer in the polymerizable composition is, for example, 1% by mass or more and 20% by mass or less.

[0044] Examples of the polymerization initiator include benzoyl peroxide, p-chlorobenzoyl peroxide, decanoyl peroxide, lauroyl peroxide, acetyl peroxide, tert-butyl (2-ethylhexanoyl) peroxide hexanoate, and tert-butyl peroxyoctoate.

[0045] The proportion of the polymerization initiator in the polymerizable composition is, for example, 0.1% by mass or more and 15% by mass or less, and preferably 1% by mass or more and 10% by mass or less.

[0046] Other additives contained in the polymerizable composition include a polymerization inhibitor, a hydrochloric acid scavenger, and the like. EXAMPLES

[0047] Comparative Example 1 First, a multifilament woven fabric of LLDPE resin was prepared as a substrate. The opening ratio of this woven fabric was 5%, the porosity was 50%, and the thickness was 208 μm. The melt mass flow rate of the LLDPE resin was 0.9 g / 10 min, the weight average molecular weight (Mw) was 265,000, and the crystallinity was 34%.

[0048] The plain weave fabric was filled with a polymerizable composition to obtain a first composite membrane. The first composite membrane was held at 30°C for 10 minutes, then heated to 90°C at a heating rate of 1°C / min, and thermally polymerized at 90°C for 180 minutes to obtain a second composite membrane. As the polymerizable composition, a mixture of 83 parts by mass of styrene, 17 parts by mass of a 55% divinylbenzene solution, 23 parts by mass of low-density polyethylene resin powder, 5 parts by mass of dibutyl phthalate, and 3 parts by mass of benzoyl peroxide was used. The average particle size of the low-density polyethylene resin powder measured by the Coulter method was 8 μm.

[0049] The second composite membrane was immersed in chlorosulfonic acid at 40° C. for 2 hours to obtain a cation exchange membrane having sulfonic acid groups introduced therein.

[0050] (Examples 1 to 17, Comparative Examples 2 to 4) An ion exchange membrane was obtained in the same manner as in Comparative Example 1, except that the formulation of the polymerizable composition and the production conditions were changed as shown in Table 1 or Table 2.

[0051] The average particle size of the polyvinyl chloride (PVC) resin powder measured by the Coulter method was 0.3 μm.

[0052] (Reference example 1) An ion exchange membrane was obtained in the same manner as in Comparative Example 1, except that a PVC resin woven fabric was used as the substrate instead of the LLDPE resin woven fabric, and a PVC resin powder was used as the thickener instead of the LDPE resin powder. The PVC woven fabric had an opening rate of 5%, a porosity of 54%, and a thickness of 80 μm.

[0053] (Reference example 2~Reference example 6) An ion exchange membrane was obtained in the same manner as in Reference Example 1, except that the formulation of the polymerizable composition and the production conditions were changed as shown in Table 1 or Table 2.

[0054] <Evaluation> (Adhesion) The surfaces of the ion exchange membranes obtained in the Examples and Comparative Examples were visually observed to check whether the resin had peeled off from the woven fabric. The evaluation criteria were as follows. The results are shown in Tables 1 and 2.

[0055] 1: No peeling 2: A small amount of resin has peeled off from the base material 3: A medium amount of resin has peeled off from the substrate 4: A large amount of resin has peeled off from the base material (Toughness per cross-sectional area) The toughness per cross-sectional area of ​​the ion exchange membranes obtained in Examples 1 to 3, Comparative Example 1, and Reference Examples 1 to 4 was measured by the following method. The ion exchange membranes in a wet state were punched out to a width of 1 cm and a length of 6 cm, and the thickness was measured at three points to obtain the average thickness. The cross-sectional area [mm 2Next, a tensile test was conducted on this ion exchange membrane. In order to prevent the ion exchange membrane from drying out during the measurement, pure water was sprayed once every 30 seconds using a spray bottle. The integral value of the test force [N]-displacement [m] curve from the initial tensile test to the breakage was taken as the toughness [J], and the toughness per cross-sectional area [J / mm2] was calculated using the cross-sectional area of ​​the wet ion exchange membrane used in the test. 2 The measurement was performed using a Shimadzu AGS-500NX measuring device. The measurement conditions were a gripping distance of 300 mm and a tensile speed of 5 mm / min. The results are shown in Tables 1 and 2.

[0056] [Table 1]

[0057] [Table 2]

Claims

1. A method for producing an ion exchange membrane comprising a substrate containing a linear low-density polyethylene resin and an ion exchange resin supported on the substrate, comprising: Filling the substrate with a polymerizable composition for forming the ion exchange resin to obtain a first composite membrane; thermally polymerizing the first composite membrane at 100° C. or more and 120° C. or less to obtain a second composite membrane; introducing an ion exchange group into the second composite membrane to obtain an ion exchange membrane; A method for producing an ion exchange membrane comprising the steps of:

2. The linear low-density polyethylene resin has a melt mass flow rate of 0.1 g / 10 min or more and 15 g / 10 min or less, measured in accordance with Japanese Industrial Standard K7210-1 under conditions of a temperature of 190 ° C. and a load of 2.16 kg.

3. The method of claim 1 , wherein the substrate comprises fibers of a linear low density polyethylene resin.

4. The method of claim 1 , wherein the polymerizable composition comprises a styrenic monomer and a crosslinking agent.

5. The method of claim 1 , wherein the polymerizable composition comprises particles of polyethylene resin.

6. The method of claim 3 , wherein the polyethylene resin of the particles comprises a low density polyethylene resin.

Citation Information

Patent Citations

  • Production of ion exchange membrane

    JP1991153740A

  • Ion exchange membrane

    JP1994322156A